Factors associated with level of glycaemic control among type 2 diabetes mellitus patients in selected health clinics in Kuala Selangor, Malaysia - Abdullah, Nurul Ain (2018)
Introduction: Type 2 diabetes mellitus (T2DM) is the most common form of diabetes affecting more people worldwide. Aims and objectives: The objective of this study is to determine the factors associated with glycaemic control (HbA1c) among T2DM patient at Klinik Kesihatan Sungai Tengi Kanan and Klinik Kesihatan Tanjung Karang, Kuala Selangor. The factors assessed were socio-demographic characteristics, T2DM medical history, diabetes knowledge, health literacy, adherence to treatment, diabetes self-care activity, diabetes quality of life, physical activity body mass index (BMI) and level of glycaemic control. Method: This is a cross - sectional study. 200 T2DM patients selected by random sampling received a guided self - administered questionnaire. The questionnaire consisted of socio-demographic variables, T2DM medical history, Michigan Diabetes Knowledge Test (MDKT), Short Test of Functional Health Literature in Adult (S-TOFHLA), adherence to treatment, Summary of Diabetes Self-care Activity (SDSCA), Diabetic Quality of Life (DQoL), International Physical Activity Questionnaire (IPAQ), BMI and HBA1c readings. To test the association between variables, the Chi - square test was used. Multiple logistic regressions have been used to find the predictors of good glycaemic control. Results: The response rate was 87.7%. The factors associated with the level of glycaemic control was the duration of diagnosed with T2DM, type of treatment obtained, blood glucose monitoring, diabetes quality of life (Worry) and BMI (p<0.05). The predictors of good glycaemic control were the duration of diagnosed with T2DM lower than 10 years and blood glucose monitoring. The probability of respondents diagnosed with T2DM below than 10 years was two times more likely to have good glycaemic control (AOR=2.458, 95% of CI=1.504-14.282, p=0.050). The odds of having good glycaemic control is higher with increasing frequency of blood glucose monitoring (AOR=1.341, 95% of CI=1.041-1.727, p-value=0.023). Conclusion: Duration diagnosed with T2DM, type of treatment obtained, blood glucose monitoring, worry and BMI were significantly associated with glycaemic control levels. The predictors of good glycaemic control were diagnosed with T2DM for less than 10 years and self blood glucose monitoring.